The First Hebrew Shakespeare Translations Isaac Edward Salkinson's Ithiel the Cushite of Venice and Ram and Jael - Khan, Lily (UCL Press, 2017)
This first bilingual edition and analysis of the earliest Shakespeare plays translated into Hebrew - Isaac Edward Salkinson's Ithiel the Cushite of Venice (Othello) and Ram and Jael (Romeo and Juliet) - offers a fascinating and unique perspective on global Shakespeare. Differing significantly from the original English, the translations are replete with biblical, rabbinic, and medieval Hebrew textual references and reflect a profoundly Jewish religious and cultural setting. The volume includes the full text of the two Hebrew plays alongside a complete English back-translation with a commentary examining the rich array of Hebrew sources and Jewish allusions that Salkinson incorporates into his work. The edition is complemented by an introduction to the history of Jewish Shakespeare reception in Central and Eastern Europe; a survey of Salkinson's biography including discussion of his unusual status as a Jewish convert to Christianity; and an overview of his translation strategies. The book makes Salkinson's pioneering work accessible to a wide audience, and will appeal to anyone with an interest in multicultural Shakespeare, translation studies, the development of Modern Hebrew literature, and European Jewish history and culture.